1999
DOI: 10.1259/bjr.72.855.10396216
|View full text |Cite
|
Sign up to set email alerts
|

The 4 year outcome following the demonstration of bilateral renal pelvic dilatation on pre-natal renal ultrasound.

Abstract: There is little in the literature regarding long-term prognosis in cases of fetal pyelectasis and calyceal dilatation. The aim of this study was to correlate antenatal ultrasound findings with outcome in a large group of children, most of whom had routine antenatal mid-trimester scans. 75 babies with bilateral pyelectasis and calyceal dilatation in the pre-natal period and complete radiological and clinical data were identified over a 3 year period. Pre-natal ultrasound was correlated with results of post-nata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 18 publications
4
18
0
2
Order By: Relevance
“…Similar data were observed by Mami et al who found a complete resolution of bilateral hydronephrosis postnatally in all infants with an APPD of ≤15 mm after a follow-up of 12-14 months [11]. Broadley et al demonstrated that 39 of 42 NBs with bilateral mild isolated hydronephrosis of ≤10 mm had insignificant abnormalities; three showed progression, and two (5%) required surgery [10]. An US follow-up until the first year of life allows for the detection of these few cases of progression.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similar data were observed by Mami et al who found a complete resolution of bilateral hydronephrosis postnatally in all infants with an APPD of ≤15 mm after a follow-up of 12-14 months [11]. Broadley et al demonstrated that 39 of 42 NBs with bilateral mild isolated hydronephrosis of ≤10 mm had insignificant abnormalities; three showed progression, and two (5%) required surgery [10]. An US follow-up until the first year of life allows for the detection of these few cases of progression.…”
Section: Discussionsupporting
confidence: 79%
“…In a similar study, Broadley et al found that 42 of 179 NBs (23%) with fetal renal abnormalities had bilateral mild hydronephrosis [10]. Similar data have been reported by other authors [9,11].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This may be because of the subtlety of prenatal diagnosis in some cases, but also because of the overlap between ultrasound appearances between obstructive pathologies and those that are secondary to reflux. 21 Long-term outcomes were worse in fetuses identified prenatally and with co-existent anomalies. Parental choice of TOP was not insignificant in this cohort (and indeed in pregnancies with apparently isolated LUTO).…”
Section: Resultsmentioning
confidence: 99%
“…This may be because of the subtlety of prenatal diagnosis in some cases but also because of the overlap between ultrasound appearances between obstructive pathologies and those secondary to reflux. 105 Long-term outcomes were worse in those fetuses identified prenatally and with coexistent anomalies. Parental choice of TOP was not insignificant in this cohort (and indeed in those pregnancies with apparently isolated LUTO).…”
Section: Resultsmentioning
confidence: 99%